2013
DOI: 10.1080/15567036.2010.529568
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diesel Fuel-biodiesel-ethanol-butanol Blends on the Performance and Emission Characteristics of a Diesel Engine

Abstract: In this study, performance and exhaust emissions of a diesel engine fueled with Fuel A (60% diesel-30% biodiesel-5% ethanol-5% butanol) and Fuel B (40% diesel-50% biodiesel-5% ethanol-5% butanol) were investigated. The biodiesel produced from trap grease was obtained with an oil separator. Fuel A and Fuel B were tested in a single cylinder, four-stroke diesel engine at full load conditions. Compared with diesel fuel, the performance characteristics of blend fuels slightly deteriorated while the emission charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…First-generation palm oil biodiesel 3.7% 8% −10% [51] Second-generation waste cooking oil biodiesel 85% 85% −19.7% [52] Second-generation trap grease biodiesel 85% n.a. −5.4% [53,54] Third-generation algae 1% 5-11% −4% [54] Source: authors' composition.…”
Section: Environmental Pillarmentioning
confidence: 99%
“…First-generation palm oil biodiesel 3.7% 8% −10% [51] Second-generation waste cooking oil biodiesel 85% 85% −19.7% [52] Second-generation trap grease biodiesel 85% n.a. −5.4% [53,54] Third-generation algae 1% 5-11% −4% [54] Source: authors' composition.…”
Section: Environmental Pillarmentioning
confidence: 99%
“…The physicomechanical properties of Linas variety safflower seed are given in Table 1. Keskin et al (2013) examined the engine performance and exhaust emission values of fuel A (60% diesel, 30% biodiesel, 5% ethanol, 5% butanol) and fuel B (40% diesel-50% biodiesel-5% ethanol-5% butanol) mixture fuels, which they tested in a single-cylinder, four-stroke diesel engine under full load conditions, in comparison with diesel fuel. As a result of the study, they stated that the emission values of the blended fuels showed a significant improvement compared to the diesel fuel and that the emission values of fuel B, carbon monoxide (CO) and, hydrocarbon (HC), decreased by 87.01% and 87.50%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of alcohol as alternative fuel decreased air pollution and dependence on petroleum based fuel. Alcohols can be produced domestically from biomass crop such as wood, wheat, sugar cane and grass [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of diesel engines, important advantages of alcohol are lower viscosity and higher oxygen content. Oxygen atoms in the molecular structure of alcohols improve combustion efficiency and emission characteristics of diesel engines [3]. Important disadvantages are lower Cetane number and lower heating values [6][7][8].…”
Section: Introductionmentioning
confidence: 99%